American homicide - Roth, Randolph (Belknap Press of Harvard University Press, 2009)
"Cuttinge one anothers throates" : homicide in early modern Europe and America -- "All hanging together" : the decline of homicide in the Colonial Period -- Family and intimate homicide in the first two centuries -- "A sense of their rights" : homicide in the age of revolution -- The emergence of regional differences : homicide in the postrevolutionary period -- The rise in family and intimate homicide in the nineteenth century -- "All is confusion, excitement and distrust" : America becomes a homicidal nation -- The modern pattern is set : homicide from the end of Reconstruction to World War I -- The problem endures : homicide from World War I to the present -- Conclusion : can America's homicide problem be solved?